A Bipedicled Lip Switch Flap From the Upper Lip for Delayed Re-Do Total Lower Lip Reconstruction: A Case Report. Issue 2 (June 2022) - O'Neill, Elizabeth S.; Lee, Subin; Bonett, Andrew; Seu, Michelle Y.; Dorafshar, Amir H.
Several different techniques have been described for reconstructing vermilion lip defects. The key to successful reconstruction of the vermilion is to restore the original esthetic landmarks and appearance of the lip while preserving function. We present a case of a 49-year-old patient with a history of lower lip squamous cell carcinoma who presented to our institution status post resection and reconstruction with Bernard-von Burow cheek advancement flaps with Webster modification at an outside hospital. Her main complaint was the lack of lower lip vermillion and loss of lip height. This new defect was repaired using a bipedicled lip switch flap from the upper to lower lip. To our knowledge, this is the first time this technique has been reported in the literature to reconstruct a total vermilion lower lip defect. A bipedicled lip switch flap offers an alternative, reliable method for the repair of large vermilion lip defects that can produce satisfactory esthetic and functional outcomes.